The Road to modern art 1800-1900 (The National Gallery - A Private View, 1986)
Features works of Delacroix, Courbe, Corot, Cezanne, Pisarro, Monet, Manet, Renoir, Degas, Seurat, Van Gogh, and Rousseau.